An activity-based workload modelling approach for determining diagnostic radiographer staffing requirements within a diagnostic radiology practice. - Cloete, Cosmo (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.